2018
DOI: 10.1257/aer.20151362
|View full text |Cite
|
Sign up to set email alerts
|

Do Larger Health Insurance Subsidies Benefit Patients or Producers? Evidence from Medicare Advantage

Abstract: A central question in the debate over privatized Medicare is whether increased government payments to private Medicare Advantage (MA) plans generate lower premiums for consumers or higher profits for producers. Using difference‑in‑differences variation brought about by a sharp legislative change, we find that MA insurers pass through 45 percent of increased payments in lower premiums and an additional 9 percent in more generous benefits. We show that advantageous selection into MA cannot explain this incomplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 40 publications
3
35
1
Order By: Relevance
“…The efficient outcome is at point c, full enrollment, because in this example the demand curve is everywhere above the marginal cost curve, implying that willingness-to-pay exceeds individualspecific marginal costs to the plan for every individual. 4 Here, society as a whole (consumers + insurers) would be made better off if all consumers took up insurance.…”
Section: Subsidies and Penalties Related To Taking Up Health Insurancementioning
confidence: 99%
“…The efficient outcome is at point c, full enrollment, because in this example the demand curve is everywhere above the marginal cost curve, implying that willingness-to-pay exceeds individualspecific marginal costs to the plan for every individual. 4 Here, society as a whole (consumers + insurers) would be made better off if all consumers took up insurance.…”
Section: Subsidies and Penalties Related To Taking Up Health Insurancementioning
confidence: 99%
“…Previous research has demonstrated that the county benchmark payment rates used to determine capitated payment amounts for all MA plans, including D‐SNPs, have important effects on the market for regular MA plans. Larger benchmarks have been found to increase the availability of regular plans, insurer entry into MA markets, the generosity of benefits offered, regular MA enrollment, and insurer profits …”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In a 2018 study, Pelech examines pre‐ACA policy changes impacting private fee‐for‐service (PFFS) plans, finding that reductions in county‐level plan offerings led to an increase in expected enrollee out‐of‐pocket spending and higher premiums for PFFS plans . A 2014 study by Cabral et al exploits the introduction of MA payment floors in 2000, finding that, among plans receiving higher payments, greater market share was associated with lower “pass through” of those payments to enrollees in the form of reduced premiums . McCarthy and Darden's 2017 study examines the impact of MA quality ratings on premiums and plan offerings for 2009‐10, finding that contracts receiving higher star ratings raised their premiums in the subsequent year .…”
Section: Relevant Literaturementioning
confidence: 99%